2010
DOI: 10.1039/b9ay00193j
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic analysis of major non-structural carbohydrates in several wood species – an analytical approach for higher accuracy of data

Abstract: The exact and reliable determination of non-structural carbohydrates (NSC) in wood samples of different origin allows to gain further insight into the biogeochemical carbon cycle, i.e. processes that determine how carbon -and carbon dioxide -migrate between the land, the sea and the atmosphere. Plants are an essential part of this cycle using carbon dioxide in photosynthesis and locking up carbon within proteins and carbohydrates. Analytical determination of NSC is complicated by the complexity of the carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…These results may be attributed to the higher efficiency of starch extraction and hydrolysis with HClO 4 in comparison with HCl. According to Raessler et al (2010), the accurate determination of starch is dependent on both its complete extraction from the sample and its complete hydrolysis into glucose. In green algae, starch is synthesized and stored within the chloroplast, which considerably limits the accessibility of the solvent during extraction.…”
Section: Resultsmentioning
confidence: 99%
“…These results may be attributed to the higher efficiency of starch extraction and hydrolysis with HClO 4 in comparison with HCl. According to Raessler et al (2010), the accurate determination of starch is dependent on both its complete extraction from the sample and its complete hydrolysis into glucose. In green algae, starch is synthesized and stored within the chloroplast, which considerably limits the accessibility of the solvent during extraction.…”
Section: Resultsmentioning
confidence: 99%
“…The extracts were then evaporated further under a stream of nitrogen to obtain residues that were dried in vacuo over a desiccant (Drierite) before weighing. Aqueous extracts, likely comprising water-soluble non-structural carbohydrates (Raessler et al 2010), extractives, and inorganics, were freeze dried and weighed. The extractive-free inner bark and outer bark tissues were dried in an oven (100°C) before weighing.…”
Section: Extractive Analysismentioning
confidence: 99%
“…Though elevated temperatures solubilize starch (Mangalam 2005), wood thermolysis/pyrolysis can result not only in carbohydrate degradation but also in depolymerization of structural fractions such as lignin and cellulose (Mangalam 2005), thereby destroying the structural integrity of yam sticks. Though a hot water extraction helped release the carbohydrates and starch for NSC determination without affecting structural carbohydrates, Raessler et al (2010) found that even at temperatures slightly lower than 100°C, carbohydrate values were only slightly higher with hot water extraction than with coldwater extraction. Based on these findings, heating water below 100°C to extract starch from in situ (unmashed) bamboo would largely be a waste of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable quantities of starch in green or dry bamboo make it more attractive to organisms such as stain fungi and borer beetles (Wahab et al 2009). Non-structural carbohydrates (NSC) consisting of sugar alcohols such as inositol, sorbitol, and mannitol; monosaccharides, such as glucose and fructose; disaccharides such as sucrose; oligosaccharides such as raffinose and starch (Raessler et al 2010) are the main nutrients in bamboo for the abovementioned biological agents.…”
Section: Introductionmentioning
confidence: 99%